A high-androgen microenvironment inhibits granulosa cell proliferation and alters cell identity. (1st July 2021) - McFee, Renee M.; Romereim, Sarah M.; Snider, Alexandria P.; Summers, Adam F.; Pohlmeier, William E.; Kurz, Scott G.; Cushman, Robert A.; Davis, John S.; Wood, Jennifer R.; Cupp, Andrea S.
Abstract: A naturally occurring bovine model with excess follicular fluid androstenedione (High A4), reduced fertility, and polycystic ovary syndrome (PCOS)-like characteristics has been identified. We hypothesized High A4 granulosa cells (GCs) would exhibit altered cell proliferation and/or steroidogenesis. Microarrays of Control and High A4 GCs combined with Ingenuity Pathway Analysis indicated that High A4 GCs had cell cycle inhibition and increased expression of microRNAs that inhibit cell cycle genes. Granulosa cell culture confirmed that A4 treatment decreased GC proliferation, increased anti-Müllerian hormone, and increased mRNA for CTNNBIP1 . Increased CTNNBIP1 prevents CTNNB1 from interacting with members of the WNT signaling pathway thereby inhibiting the cell cycle. Expression of CYP17A1 was upregulated in High A4 GCs presumably due to reduced FOS mRNA expression compared to Control granulosa cells. Furthermore, comparisons of High A4 GC with thecal and luteal cell transcriptomes indicated an altered cellular identity and function contributing to a PCOS-like phenotype. Graphical abstract: Image 1 Highlights: Bovine granulosa cell gene expression in excess androgen microenvironment. Androgen excess causes cell cycle arrest and increased AMH expression in granulosa cells. Increased AMH contributs to increased CTNNBIP1 which reduces granulosa cell proliferation. Reduced FOS abundance in excess androgen granulosa cell microenvironment correlates with increased CYP17A1 . Androgen excess microenvironment correlates with increased miRNA which target cell cycle genes.